SHEARER, Vernon Lyall Inventory of documents - SHEARER, Vernon Lyall (ARCA, 2018)
Private papers of V.L. Shearer, MP Durban-Point [1938-1958], for the Dominion Party [1938-1943], Independent [1943-1948], United Party [1948-1954], National Conservative Party [1954-1957], Independent [1957-1958], Mayor of Durban [1964-1966]
COVERAGE 1933-1968; 233 Files; 3,89 Metres.
Keywords: SHEARER, Vernon Lyall; Inventories; Politicians